Biosynthesis of peptidoglycan in Gaffkya homari: on the target(s) of benzylpenicillin. - Sinha, R K (1991)
The formation of acceptor for the N epsilon-(D-Ala)-acceptor transpeptidase is an essential feature of nascent peptidoglycan processing. In Gaffkya homari the synthesis of cross-bridges in peptidoglycan includes a variety of penicillin-sensitive enzymes, e.g., transpeptidase, DD-carboxypeptidase, and LD-carboxypeptidase. To determine the primary target, we grew cultures in the presence of the MICs of benzylpenicillin (0.2 microgram/ml), methicillin (10 micrograms/ml), cephalothin (5 micrograms/ml), and cefoxitin (25 micrograms/ml) and examined the monomer-dimer composition of each peptidoglycan by high-performance liquid chromatography after muramidase digestion. From these studies it was recognized that of all the dimers, the synthesis of the predominant cross-bridge, diamidated octapeptide (-Ala-iso-D-Gln-Lys-D-Ala -Ala-iso-D-Gln-Lys-D-Ala), is most sensitive to the action of the beta-lactam at its MIC. The enhanced deamidation of the acceptor tetrapeptide, one of the substrates for the transpeptidase, is correlated with the inhibition of this cross-bridge. For example, at the MIC of benzylpenicillin, the ratio of amidated tetrapeptide to nonamidated tetrapeptide decreased from 2.8 in the control to 1.0 in the treated culture. From these results it would appear that a decrease in preferred acceptor for the transpeptidase results in the inhibition of synthesis of this major cross-bridge. Thus, the metabolism of the amide function of the monomer peptides may represent an additional feature of processing in the assembly of cross-bridged dimers in the peptidoglycan of this organism that is sensitive to the action of beta-lactam.